IDENTIFICATION OF SEDIMENT PROPERTIES DEGRADATION OF DELTA CIMANUK DEPOSIT BASED ON STRATA BOX DATA - Riza Rahardiawan (Pusbindiklat - LIPI, 2013)
Knowledge on physical properties of seafloor sediments is essential in planning offshore construction, in particular oil and gas construction. Changes in the physical properties of sediments such as faults and fractures, as well as the presence of gas within seafloor sediments can be detected as a decrease in acoustic wave velocity due to reduction in sediment shear strength. Normalization of Cimanuk River in early 1980s has resulted in higher sediment influx and increasing rate of compaction that change the physical properties of the sediment. Analysis of amplitude and wave velocity using software SonarWiz 5 on the records obtained from sounding equipment: Sub-Bottom Profiler type ODEC Strata Box and Bathy 1500, show significant change in wave speed that is caused by shallow gas seepage associated with fractures in the Polygonal Fault System (PFS ). This fault system formed as a result of diagenetic processes of fine grain sediment and reduction of the sediment shear strength due to accumulated sediment cover. Shallow gas seepage itself is commonly found in organic-rich marine sediments and are usually composed of methane.